The Use of Active Remote Sensing Data and Adaptive Threshold Method for Analysing Oil Spill in West Side of Java Sea - Bhisma Kusuma Wardhana; Filsa Bioresita; Noorlaila Hayati (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2025)
Oil spill phenomena, particularly in the West Side of Java Sea, occur due to the dense oil industry and maritime activities causing potential vulnerability to oil pollution. Rapid detection of oil spill distribution needs to be conducted to minimize the resulting impacts. By developing an early detection method for oil spills in the Western Java Sea using Synthetic Aperture Radar (SAR) technology from Sentinel-1A Satellite using SNAP software with an Adaptive Threshold approach. The detection method is based on the principle that oil causes the sea surface to become calm, resulting in a drastic reduction in radar wave reflection values. Research results show oil spill detection in June 2023 with an area reaching 73,823 km² and an accuracy level of 93,75% based on confusion matrix validation. This research also integrates windfield analysis to support radar image interpretation, with wind speed estimation results of 1-12 m/s and dominant direction toward northwest to north. Windfield data was validated using BMKG reanalysis data and Copernicus Marine My Ocean Pro. The developed method is superior to optical imagery in terms of detection visualization and object classification capability within the spill area. The findings of this research provide important contributions to the development of effective monitoring and response systems to protect marine ecosystems, and can serve as a basis for planning environmental impact mitigation from oil spills in the region.